KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA MELALUI PENERAPAN MODEL PROBLEM BASED LEARNING DI SMPN 1 PANTE CEUREUMEN - Uci Mahlisa; Nursiah (LPPM Universitas Cipta Mandiri, 2025)
Education is the most fundamental factor for human life. Education aims to foster various potentials in humans, including the potential to solve various problems, one of which is solving mathematical problems. This study aims to describe students' problem-solving abilities during mathematics learning on social arithmetic material with the Problem Based Learning (PBL) model implemented in class VIIA of SMPN 1 Pante Ceureumen, totaling 25 students. The study used a qualitative approach with a descriptive research type. To obtain research data, treatment, problem-solving tests, and interviews were given. The research subjects were taken after a test was conducted at the end of the meeting, so that 2 subjects with very capable abilities, 2 subjects with capable abilities, and 2 subjects with less capable abilities were obtained. Furthermore, interviews were conducted with the six subjects. After all the data was collected, the qualitative data was analyzed descriptively, while the test result data was analyzed based on the guidelines for assessing students' problem-solving abilities. Based on the analysis of the data, it can be concluded that students' problem-solving abilities through the application of the PBL model are influenced by students' mathematical abilities. Therefore, this model can be one solution that can be applied to arouse students' enthusiasm for learning in class.